Geochemical Constraints Provided by the Freetown Layered Complex (Sierra Leone) on the Origin of High-Ti Tholeiitic CAMP Magmas - Callegaro, Sara; Marzoli, Andrea; Bertrand, Herve´; Blichert-Toft, Janne; Reisberg, Laurie; Cavazzini, Giancarlo; Jourdan, Fred; Davies, Joshua H.F.L.; Parisio, Laura; Bouchet, Romain; Paul, Andre; Schaltegger, Urs; et al. (Journal of Petrology, 2018)
The Freetown Layered Complex (FLC) is a massive mafic layered intrusion cropping out along the coast of Sierra Leone. The present combined geochemical and geochronological (40Ar/39Ar on plagioclase: 201·7 ± 0·7 and 202·3 ± 2·3 Ma; U–Pb on baddeleyite: 198·794 ± 0·048/0·071/0·22 Ma) study of the complex flags it as a high-Ti occurrence of the Central Atlantic Magmatic Province (CAMP). Sr–Nd–Pb–Os isotope data indicate that the FLC is unique with respect to previously studied CAMP occurrences, constituting a new isotopic end-member for this large igneous province (LIP). Notably, the contribution of ancient source(s) is required to explain its low 206Pb/204Pb and high 207Pb/204Pb. Although the internal isotopic variability of the FLC can be explained by modest assimilation (<10%) of lower crustal (granulitic) material, represented by a xenolith found within the complex itself, an atypical mantle source is required to account for its unusual Pb isotopic composition. We also present the first Hf isotopic data measured to date for CAMP rocks, which, in the case of the FLC, show a restricted range in 176Hf/177Hf, overlapping the ocean island basalt and mid-ocean ridge basalt fields on the terrestrial array, and can further be used to characterize the FLC isotopic end-member. We propose that the FLC formed by mixing of a predominantly asthenospheric parental magma with small volumes (1–3%) of geochemically highly enriched lamproitic melts derived from the sub-continental lithospheric mantle in a geodynamic context in which a Proterozoic mobile belt (Rokelide) bordered an Archean craton (Man). Within the CAMP, similar isotopic compositions, in particular low 206Pb/204Pb and high 207Pb/204Pb, are found only in regions that were once contiguous with Sierra Leone. A comparable involvement of enriched components stored within the cratonic lithosphere may be envisaged for the high-Ti magmatism in the CAMP and two other LIPs of the South Atlantic realm, Karoo and Paraná–Etendeka. These Gondwana magmatic provinces share with other mantle-derived magmas from the South Atlantic Ocean enriched isotopic signatures (DUPAL, LOMU, EMI) of much debated origin. The present mantle source model for the FLC, CAMP, and neighbouring LIPs suggests ancient enriched subcontinental lithospheric mantle as a plausible conveyor of such isotopic signatures in the South and Central Atlantic. © 2017 Oxford University Press